Case Report: Successful Stabilization of Marburg Variant Multiple Sclerosis With Ocrelizumab Following High-Dose Cyclophosphamide Rescue - Koska, Valeria; Förster, Moritz; Brouzou, Katja; Hatami, Maryam; Arat, Ercan; Aytulun, Ahmet; Albrecht, Philipp; Aktas, Orhan; Küry, Patrick; Meuth, Sven G.; Kremer, David (Frontiers in Neurology, 2021)
The Marburg variant of multiple sclerosis (Marburg MS) is the most aggressive form of MS often leading to death soon after onset. Here, we describe the case of a 26-year-old Marburg MS patient presenting with severe neurological deficits requiring intensive care. In spite of more than 100 Gadolinium-enhancing MRI lesions the patient recovered almost completely upon high dose cyclophosphamide (HiCy) rescue treatment (four consecutive days with 50 mg/kg/day, cumulative absolute dose of 14 g). Following acute treatment her disease was stabilized by B cell depletion using ocrelizumab. Clinical amelioration was reflected by a decrease of MRI activity and a marked decline of serum neurofilament light chain (NfL) levels. HiCy rescue treatment followed by ocrelizumab as a maintenance therapy prevents permanent disability and achieves an almost complete clinical and drastic radiological improvement in this Marburg MS patient.